Eliade și Sebastian - Dumitru Micu (Revista de Istorie și Teorie Literară)
The article presents the friendship between Mircea Eliade and Mihail Sebastian in the light of the two authors’ perspectives on each other’s works. While Eliade considers that Sebastian, who died in 1945 in a tragic car accident, would have become a great literary critic, Sebastian comments upon Eliade’s prose, especially Domnisoara Christina and Maitreyi, as the most important Romanian literary achievements in the field of fantastic genre since Eminescu’s Sarmanul Dionis.